Novičarski dejavniki in internetna družbena omrežja - Milosavljevič, Marko (Javnost (Ljubljana), 2014)
Within the processes of permanent transformations and upgrades of new technological/communication platforms and formats, journalism is also reconfiguring its position within the society. This includes all of the phases: collecting information, production and distribution, including the process of selecting news content based on news values. An important research gap was present regarding the analysis of the use of content from the Twitter in news content and news criteria that are the basis for the editorial decisions about such use. The article presents the news and contextual criteria/values that are used to define which tweets will be chosen and used in news reporting on European Parliament elections 2014, based on in-depth semi-structured interviews with editors of Slovene news media. On the basis of these interviews, the following classification of criteria was established: timeliness and speed; composition (establishing adequate news net); Twitter as a topic; relevancy and elite individuals; editorial policy and world view; conflict; entertainment; exclusivity or limited access; medium or technology; and frequency. An important shift in the structure of news values is found: the substantive values are less present than product values and competition values, as well as wider, structural values. This shows an emphasis placed on Twitter as medium and its characteristics that overshadow the content aspects and strengthen other aspects.
Keywords: European Union; Evropska unija; Evropski parlament; election; volitve; politične komunikacije; mass media; množični mediji; informiranje; journalism; novinarstvo; družbena omrežja